Future Giant Telescopes 2003
DOI: 10.1117/12.458150
|View full text |Cite
|
Sign up to set email alerts
|

Control of the California Extremely Large Telescope primary mirror

Abstract: The current design concept for the California Extremely Large Telescope (CELT) includes 1080 segments in the primary mirror, with the out-of-plane degrees of freedom actively controlled. We construct the control matrix for this active control system, and describe its singular modes and sensor noise propagation. Data from the Keck telescopes are used to generate realistic estimates of the control system contributions to the CELT wavefront error and wavefront gradient error. Based on these estimates, control sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 7 publications
(5 reference statements)
0
13
0
Order By: Relevance
“…We considered this question in detail elsewhere 19,20 and concluded that a supplementary wave-front sensor is not likely to be needed for stabilization purposes. Here we just summarize the argument.…”
Section: Error Multipliers From Singular-value Decompositionmentioning
confidence: 99%
“…We considered this question in detail elsewhere 19,20 and concluded that a supplementary wave-front sensor is not likely to be needed for stabilization purposes. Here we just summarize the argument.…”
Section: Error Multipliers From Singular-value Decompositionmentioning
confidence: 99%
“…If additional sensors are also used ͑such as wave-front information͒, then y can be expanded to include both sets of measurements. The baseline disturbance rejection control algorithm 5,12 can be divided into two steps, shown in Fig. 2.…”
Section: Control Analysismentioning
confidence: 99%
“…The average over these data sets of the estimated residual surface error at Keck due to uncontrolled low-frequency vibration is 50 -75 nm. 14 The low-frequency spectrum is of primary interest for assessment of control system noise, and the sensor noise level is estimated with the approach outlined above. Figure 6 shows the correlation between the low-frequency energy in the physical and unphysical components for Keck 1, averaged over 0 -2.5 Hz and from 2.5 to 5 Hz.…”
Section: Analysis Of Keck Sensor Datamentioning
confidence: 99%
“…MacMartin [52]. The wind disturbance, shown here as an input to the plant, is represented as frequency based disturbance spectra.…”
Section: Tmt Model and Fidelitymentioning
confidence: 99%